Migration and the Problem of Old Age People in Nepal - Gautam, Tika Ram (Dhaulagiri Journal of Sociology and Anthropology, 2008)
Current trends of migration in Nepal imply that the extensive out-migration of young people from rural areas, to foreign and internal urban centres, coincides with a rise in the problem of older couples in rural areas. This article examines the impact of migration on living condition and internal feelings of old age couples by drawing on the results of sociological and demographic field studies in Kandebash Village Development Committee (VDC) comprising multiethnic communities of western Nepal. The methodology for identifying older people is, social survey followed by direct interview with semi-structured questionnaire, examining variations by socio-economic strata and family structures. Comparative analysis indicates considerable heterogeneity in past and present migration patterns, both within and between countries. Economically higher status families are commonly able to reinforce their position by making better use of emigration opportunities. These families are migrating permanently to urban centers within country. Migrants from economically middle and lower status families are continuing temporary migration to foreign countries. Temporary migration, both within and between countries, is making old age couples alone in rural villages. The migrants' financial and material contributions are a nominal support. The old age lonely couples are facing many problems such as feeling loneliness, helplessness, frustration, increased household and social burdening. Key words: Migration, emigration, immigration, old age couple, rural migration, Nepal DOI = 10.3126/dsaj.v2i0.1361 Dhaulagiri Journal of Sociology and Anthropology Vol.2 pp.145-160